ANALISIS E-GOVERNMENT TERHADAP PELAYANAN PUBLIK PADA DIREKTORAT JENDERAL KEPENDUDUKAN&PENCATATAN SIPIL KEMENTERIAN DALAM NEGERI - Arih Setyaningrum; Evi Satispi; Risya Amalia (Universitas 17 Agustus 1945 Semarang, Indonesia, 2023)
E-government which can be broadly defined as the utilization of information and communication technology and the internet which has the ability to transform relations with citizens, business people and other government institutions. The development of Information and Communication Technology (ICT) is currently very rapid and of course it must be addressed positively to increase community participation in realizing the principles of good governance (Good Governance). This study uses a qualitative research method with a descriptive approach. Sources of data in this study are observation, literature, articles, journals, scientific research and sites on the internet. The Ministry of Home Affairs has a public service unit, one of which is the Directorate General of Population & Civil Registration, of course it is required to provide optimal service to the community. The implementation of e-government, related to service and dissemination of public information at the Ministry, especially at the Directorate General of Population and Civil Registration is already good and in the medium category, and still needs to be repaired and improved. The Ministry of Home Affairs in implementing e-government fulfills the first stage, namely information publishing and the two